2021
DOI: 10.1016/j.chaos.2021.110895
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainty quantification of a mathematical model of COVID-19 transmission dynamics with mass vaccination strategy

Abstract: In this paper, the uncertainty quantification and sensitivity analysis of a mathematical model of the SARS-CoV-2 virus transmission dynamics with mass vaccination strategy has been carried out. More specifically, a compartmental epidemic model has been considered, in which vaccination, social distance measures, and testing of susceptible individuals have been included. Since the application of these mitigation measures entails a degree of uncertainty, the effects of the uncertainty about the application of soc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 30 publications
0
50
0
Order By: Relevance
“…It is important however to note that while therapeutic measures, vaccination, and treatment are very effective in curtailing the spread of the epidemic, more control efforts are required to eradicate the disease when R 0 ( v ) > 1. Thus, continuously and concurrently applying both pharmaceutical and nonpharmaceutical public health interventions such as face mask, hand washing, and social distancing should be encouraged [ 64 ].…”
Section: Numerical Simulationsmentioning
confidence: 99%
“…It is important however to note that while therapeutic measures, vaccination, and treatment are very effective in curtailing the spread of the epidemic, more control efforts are required to eradicate the disease when R 0 ( v ) > 1. Thus, continuously and concurrently applying both pharmaceutical and nonpharmaceutical public health interventions such as face mask, hand washing, and social distancing should be encouraged [ 64 ].…”
Section: Numerical Simulationsmentioning
confidence: 99%
“…Models developed by Olivares and Stafetti (2021) showed that even a mass vaccination with one million inoculations per week during six months would only produce 15–18% of acquired immunity. That would add the proportion of immunized individuals to 46–59% of the total population that is still not sufficient for reaching herd immunity [ 24 ]. With limited vaccine availability and health care capacity, optimal protection could not be reached.…”
Section: Discussionmentioning
confidence: 99%
“…A modified SEIR compartmental model, introduced in [13] and denoted as SEIsIaQR, is used in this paper to represent the COVID-19 transmission dynamics, in which, following [16] , a vaccination term is added to the model as shown in Figure 1 .
Fig.
…”
Section: Methodsmentioning
confidence: 99%